Avaliação da presença de dioxinas e PCBs no meio ambiente através de estudos de caso e viabilidade do uso de cromatografia gasosa acoplada a espectrometria de massas sequencial na análise destes compostos - Igor Cabreira Pussente (2016)
The polychlorinated dibenzo-p-dioxin (PCDD), polychlorinated dibenzofurans (PCDF) and 'dioxin-like' PCBs (dl-PCBs) are polyhalogenated aromatic hydrocarbons. Due to their low potential for thermal and microbiological degradation, these compounds are persistent in the environment. The number of chlorine atoms and the position where they are attached to the aromatic ring determine the toxicological potential of these compounds to animals. The human and animal exposure to these congeners has been monitored by official programs regulated by the European Union for the analysis of dioxins and PCBs in environmental and foodstuff samples. Industrial processes and other human activities, as well as undesirable incidents, are the main sources of emissions of these compounds to the environment. This work is divided in three main chapters. Hence, in Chapter 1 it is described the general aspects of dioxins and PCBs, with detailed information about these compounds, their toxicities and technical data regarding the analytical techniques performed herein. Chapter 2 presents the case study of migratory bird Northern Wheatear, in which gas chromatography coupled with high resolution mass spectrometry (GC-HRMS) is employed to analyze the toxic congeners of PCDD/Fs and dl-PCBs, as well the non-toxic NDL-PCBs. To investigate possible contamination in the bird routes, the following samples, collected during the bird reproductive cycle in the Netherlands, were analyzed: soil, eggs, embryos as well as insects and larvae of the bird food chain. The following levels were found in each sample: eggs (13.08 pg TEQ PCDD/Fs-dl-PCBs-WHO2005 g-1; 'ritnaald' larvae (7.08 pg TEQ PCDD/Fs-dl-PCBs WHO2005 g-1; soil (collected close to the bird nests: 2.21 pg TEQ PCDD/Fs-dl-PCBs-WHO2005 g-1. The comparison of the distribution profiles revealed strong evidence that some insects and larvae acquire congeners of PCDD/Fs and PCBs when in contact with soil. Then, the female transfers the contamination to the eggs upon feeding on insects. In Chapter 3, the levels of PCDD/Fs and PCBs, as analyzed by GC-HRMS, in soil samples collected in the urban area of Belo Horizonte/MG are presented. The total TEQ concentration ranged from 0.43 to 4.54 ng TEQ kg-1 dry matter (dm). The highest average level was 2.68 (± 1.63) ng TEQ kg-1 dm. The low levels achieved for all samples suggest that the investigated areas are not affected by possible sources of dioxin emissions, even knowing that Belo Horizonte is surrounded by a number of them. In Chapter 4 the performance of APGC-MS/MS as an alternative technique to GC-HRMS for the analysis of dioxins, furans and PCBs is investigated. The results of more than 200 real samples are analyzed. Hence, selectivity was assessed by comparing the chromatograms from both approaches, i. e. GC-HRMS and APGC-MS/MS. Sensitivity was considerably better for APGC-MS/MS than GC-HRMS whereas similar linear dynamic ranges were achieved for both techniques. Finally, the ratios between ions were mostly within the ± 15% tolerance range. Shortly, the determination of dioxins and PCBS by APGC-MS/MS meets the requirements defined by the European Commission. However, due to a slightly superior overall performance, the GC-HRMS technique is still the preferred method for dioxins analysis to be used for control purposes.